The Effectiveness of Prison Criminal in Changing the Behavior of Inprison-ers (Study at Class II B Penitentiary in Lubuk Pakam) - Simanjuntak, Hotmaida (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The existence and effectiveness of imprisonment in changing the behavior of convicts is quite interesting to study, considering the facts that exist show that imprisonment through the correctional system has not been able to change the behavior of convicts significantly. The problems in this study are regarding the existence of imprisonment and prison conditions as a place for implementing coaching for convicts, regarding coaching and its influence on the behavior of convicts while serving their sentences in Correctional Institutions and the effectiveness of imprisonment as the implementation of criminal sanctions and at the same time a means to change the behavior of convicts. This type of research is empirical juridical research, using a statute approach and a conceptual approach. This research uses field studies and literature studies that aim to collect primary and secondary data. The data analysis used is qualitative data analysis. Based on the results of research and discussion, imprisonment is still quite effective in changing the behavior of convicts. This is in accordance with the objectives of the penitentiary system regulated in the penitentiary law and there is also a change in the behavior of some inmates who have undergone the coaching process. The conclusion of this study is that the existence of imprisonment as a means of implementing coaching for convicts is still quite relevant to be applied in the criminal justice system in Indonesia. Considering that the implementation of imprisonment in Indonesia is not only a form of retaliation (punishment) against perpetrators, but also aims to restore the situation, namely to rehabilitate perpetrators and at the same time protect society from the perpetrator's actions to repeat his crime. Coaching carried out by Correctional Institutions has an influence on changes in the behavior of convicts. Although in the implementation of the coaching there are still various weaknesses that indicate the failure of the coaching process. Imprisonment as the implementation of criminal sanctions and at the same time a means to change the behavior of convicts is still quite effective, although it cannot be said that it is a very effective means to change the behavior of convicts.